Unsettled Visions : Contemporary Asian American Artists and the Social Imaginary - Machida, Margo (Book collections on Project MUSE., 2008)
A study of how artists of diverse Asian heritages and generational backgrounds use their artwork to articulate complex notions of identity and identification as Asians living in the United States.